Inheritance Law Study, Understanding Inheritance Without a Will: What Happens If There is No Will? - Pasla, Delma Marlina (Labor Program Studi Pendidikan Sosiologi, 2025)
This study aims to analyze the mechanism of inheritance without a will in the pluralistic Indonesian legal system, which includes Islamic law, Western civil law, and customary law. The research method used is a qualitative approach with literature study techniques through analysis of various sources such as legislation, legal textbooks, academic journals, and previous research results relevant to the topic of inheritance without a will. The results of the study indicate that each legal system has a different mechanism in regulating inheritance without a will, where Islamic law applies the imperative faraid system with distribution based on the position of the heir, Western civil law uses a class system with the principle of saisine and equal distribution for all children, while customary law relies heavily on the kinship system adopted by the local community. This pluralism of inheritance law provides options but also creates legal uncertainty and potential conflict, so it is necessary to increase public legal awareness regarding the importance of inheritance planning through wills as well as legal reform to harmonize various systems while still respecting cultural diversity and upholding the principles of justice and gender equality.